POLA ASUH ORANG TUA DALAM MENANAMKAN SIKAP DISIPLIN ANAK PADA MASA PANDEMI COVID-19 - Cahyono, Cahyono; Margiani, Veni; Intan Talitha, Rahma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
It takes proper parenting style from parents in instilling a child's discipline. The problems that are studied are how the parenting style, constraints and efforts. The research objective describes the parenting styles, constraints and efforts. The research was conducted at Rt. 33 Rw. 11 BTN Griya Mukti Indah Housing, Gembor Village, Pagaden District, Subang Regency with a qualitative approach. The subjects of this study were 10 parents who have primary school-age children or 6-12 years old. The underlying theory in parenting is the theory of Danny I Yatim. Data collection methods used were interviews, observation and documentation. Claster Sampling (area sampling) was used to prove the validity of the data. sources and methods. Data analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results showed that parents should apply parenting styles that are in accordance with the current situation, condition and development of a child. In terms of children's discipline, parents should play an active role in controlling their children's daily lives so that children are always disciplined and obey the existing rules in the family and community environment.